Cryptocurrencies, FOREX and stocks: portfolio diversification and the Russia-Ukraine war - Tan, Frederick Jia Wei (2023)
The aim of this study is to investigate how the Russia-Ukraine war could affect the diversification benefits between stock index, FOREX and cryptocurrencies. The wavelet coherence is used to examine the difference in co-movement between assets during normal and war periods and dynamic conditional correlation (DCC) is used to examine the correlation between cryptocurrencies and other assets to examine its diversification properties during war periods. Wavelet coherence results indicates that not all asset’s correlation would increase during war and international portfolio diversification benefits still exist in a globalised and integrated economy. Contagion effect is found to increase for some assets during war period. Also, the DCC proves that not all cryptocurrencies act as effective diversifiers for FOREX and stock market. However, cryptocurrencies are found to be a more effective diversifier for FOREX when compared to stock.